Prognostic significance of L-type amino acid transporter 1 (LAT1) and 4F2 heavy chain (CD98) expression in surgically resectable stage III non-small cell lung cancer - KAIRA, KYOICHI (D.A. Spandidos, 2010)
The purpose of this study was to evaluate the prognostic value of L-type amino acid transporter 1 (LAT1) and 4F2 heavy chain (CD98) expression in patients with stage III non-small cell lung cancer (NSCLC). A total of 188 consecutive patients with pathologic stage III NSCLC were retrospectively reviewed. The expression of LAT1, CD98, Ki-67 labeling index, vascular endothelial growth factor (VEGF) as well as microvessel density (MVD) were evaluated immunohistochemically and correlated with the prognosis of patients after complete resection of the tumor. Positive expression of LAT1 and CD98 was noted in 58% (109/188) and 50% (94/188) of the cases, respectively (p=0.1473). A positive rate of LAT1 expression was significantly higher in squamous cell carcinoma (SQC) (90%, 48/53) and large-cell carcinoma (LCC) (100%, 12/12) than in adenocarcinoma (AC) (40%, 49/123). Moreover, a positive rate of LAT1 with CD98 expression was also significantly higher in SQC (74%, 39/53) and LCC (75%, 9/12) than AC (34%, 42/123). LAT1 expression was significantly higher in patients with mediastinal lymph node metastases than in patients without, and was significantly correlated with CD98, Ki-67 labeling index, VEGF and MVD. The 5-year survival rates of LAT1-positive and -negative patients and CD98-positive and -negative patients were 27.9 and 40.6% (p=0.0033), respectively, and 24.1 and 43.6% (p=0.0004), respectively. Multivariate analysis confirmed that positive expression of LAT1 and CD98 was an independent factor predicting a poor prognosis. In conclusion, the overexpression of LAT1 and CD98 is a pathological factor for predicting the prognosis of patients with surgically resectable stage III NSCLC.